Exploring the landscape of immunotherapy approaches in sarcomas - Pilavaki, Pampina; Panagi, Myrofora; Arifi, Samia; Jones, Robin L.; Stylianopoulos, Triantafyllos; Constantinidou, Anastasia (Frontiers in Oncology, 2023)
Sarcomas comprise a heterogenous group of malignancies, of more than 100 different entities, arising from mesenchymal tissue, and accounting for 1% of adult malignancies. Surgery, radiotherapy and systemic therapy constitute the therapeutic armamentarium against sarcomas, with surgical excision and conventional chemotherapy, remaining the mainstay of treatment for local and advanced disease, respectively. The prognosis for patients with metastatic disease is dismal and novel therapeutic approaches are urgently required to improve survival outcomes. Immunotherapy, is a rapidly evolving field in oncology, which has been successfully applied in multiple cancers to date. Immunomodulating antibodies, adoptive cellular therapy, cancer vaccines, and cytokines have been tested in patients with different types of sarcomas through clinical trials, pilot studies, retrospective and prospective studies. The results of these studies regarding the efficacy of different types of immunotherapies in sarcomas are conflicting, and the application of immunotherapy in daily clinical practice remains limited. Additional clinical studies are ongoing in an effort to delineate the role of immunotherapy in patients with specific sarcoma subtypes.